The Significance of Eco-Theology in the Perspective of Christian Eschatology: As an Attempt to Embody the New Heavens and earth - Keriapy, Frets (Tumou Tou, 2023)
Eschatology is one of the important doctrine in Christianity. The hope of the second coming of Christ into the world is an important reflection material for human being. The second coming of Christ does not only relate to the human condition after death. The second coming of Christ on earth does not only deal with humans (the dead and the living) but the bible also says that it relates to the determination of every believer to live in the new heavens and earth where this is known as heavens and the atmosphere of heaven will be experienced by human beings who believe now and then, meaning that the mandate given by God to humans to preserve and maintain the earth is a task that is accounted for now and later eschatologically. By using a literature-based qualitative research method, the authors examine in a narrative description the meaning of Eco-Theology for Christian eschatology. Eco-Theology is a tool that can be used by humans to make people see the world from a different perspective. Eco-Theology for eschatology has its significance in which by preserving nature, humans are making a new heaven and earth that can be felt by every creature. The recommendation of this research is to use eco-theology as part of practical theology, to embody heavens and earth concretely.